Representasi Identitas Ribut Santoso Sebagai Tokoh Multi Peran di Kabupaten Lumajang - Emi Yuliastutik; Anik Juwariyah; Welly Suryandoko (Jurnal Impresi Indonesia, 2025)
Lumajang Regency, East Java, is rich in cultural heritage that has produced several local figures with significant contributions to education and the arts. One of them is Ribut Santoso, a teacher, choreographer, and dance studio owner known for his dedication to developing local art and cultural values. This research aims to analyze how Ribut Santoso's identity is constructed through his various roles and how this process contributes to the formation of his public image in society. This study uses a qualitative approach with an intrinsic case study design, focusing on a single subject with distinctive characteristics. Data were collected through in-depth interviews, participatory observations, and documentation, then analyzed using Pierre Bourdieu's theory (cultural, social, and symbolic capital) and Erving Goffman's concept of self-presentation. The findings of the study revealed that the representation of Ribut Santoso's identity emerged from the synergy between self-identification and social recognition. As a teacher, he demonstrated dedication and exemplary behavior; As a choreographer, he demonstrates creativity and originality rooted in local values; and as a studio owner, he plays the role of manager and leader of the cultural community. The study highlights the strategic role of multipurpose local figures in preserving cultural heritage and building symbolic capital in society, showing how personal identity can be a source of social and cultural strength in the modern era.